Preventing Inner Child Issue: Enhancing Empathic Communication in Parenting among Informal Workers in Kemayoran - Dhamayanti, Meilani (Indonesian Journal of Community Services Cel, 2026)
Background: Childhood trauma can impact a person's mental health both during and after adulthood. This can be caused by childhood conditions, especially within the family environment.Aims: The goal of this activity was to improve participants' ability to communicate empathetically, thereby building healthier and warmer parenting relationships. The majority of participants were informal workers facing economic pressure, lack of knowledge, and emotional exhaustion. These factors often go unnoticed, leading to verbal abuse that can potentially lead to toxic parenting styles. This can cause emotional wounds (inner child) in children, which can continue to impact the next generation.Methods: The community service method included delivering interactive materials on the concept of the inner child and its impact on children in the future. Additionally, presentations on the role of empathic communication, simulations of everyday parenting situations, and a question-and-answer session were provided to explore participants' experiences. Participants, mothers under the guidance of Pundi Rakyat in Central Jakarta, better understood the importance of empathetic communication in parenting.Result: The results of the activity demonstrated an increased understanding of mothers in responding to their children's behavior with a calmer and more reflective approach. These findings confirm that education that is applicable and close to the lives of participants is effective in promoting positive parenting in vulnerable communities.